Prevalence and determinants of depression, anxiety, and stress among IT professionals working from home in Kerala, India (International Journal of Occupational Safety and Health, 2025)
Introduction: Working from Home (WFH) has become a defining aspect of the modern work landscape, especially in the wake of the COVID-19 pandemic. The Information Technology (IT) sector, in particular, seamlessly transitioned to WFH during the pandemic, thanks to both the urgent need and the technological infrastructure supporting this alternative work arrangement. The objectives of this study were to measure the prevalence and factors associated with anxiety, stress and depression among IT professionals working from home in two districts of Kerala.Methods: Data was collected from 400 IT professionals working in four IT companies located in two districts in Kerala, through a simple random sampling method between December 2022 and March 2023. The study questionnaire consisted of two parts - the socio demographic and the Depression, Anxiety, Stress Scale (DASS) 21. Data was analyzed using IBM Statistical Package for Social Sciences V20. A p-value < 0.05 was considered statistically significant.Results: Among the study participants, 48.5% were female, majority were between 22 and 45 years and 80.25% were undergraduates. The prevalence of depression among IT professionals WFH was found to be 22.75%; 0.75% had severe and 1.5% had extremely severe depression. The prevalence of anxiety was 24%; 1.75% had severe and 2.5% had extremely severe anxiety. The prevalence of stress was 11%; 1.5% had severe and 0.25% had extremely severe stress. There was a significant association between depression, anxiety and stress with employees in the low-income rage, those working in night shift and those without a weekly day-off.Conclusion: This first study on Kerala IT professionals working from home highlights that lower income, night shifts, lack of weekly offs, substance abuse, physical inactivity, and long working hours are significantly linked to poor mental health. It underscores the need for organizational interventions to promote work-life balance, healthy lifestyles, adequate rest, and accessible mental health support to safeguard both employee well-being and productivity.